Effect of blood transfusions on oxidative stress in preterm infants - Dani, C (2004)
Objective: To confirm the increase in non-transferrin bound iron (NTBI) after packed red cell (PRC) transfusion and to evaluate the association with increased oxidative stress in preterm infants. Method: Twenty healthy preterm infants (gestational age 28.2 (2.2) weeks; birth weight 1047 (230) g), who required blood transfusion for anaemia of prematurity were prospectively studied. Serum concentrations of NTBI, total hydroperoxides (TH), and protein SH groups, and plasma total radical trapping antioxidant capability (TAC) were measured within three hours before and after PRC transfusion. The infants were transfused with 38.6 (23) ml PRCs over 5.8 (1.0) hours, at a mean age of 43.3 (25.1) days. Results: After PRC transfusion, haemoglobin concentration increased from 9.2 (1.1) to 14.6 (1.5) g/l. Mean plasma NTBI concentration after transfusion was significantly higher (0.43 (0.45) v 2.03 (1.31) µmol/l; p  =  0.001), while plasma concentrations of TH (212.3 (42.2) v 214.7 (66.3) Carr units/l) and protein SH groups (317.5 (38.8) v 353.8 (57.4) µmol/), and TAC (256.3 (36.1) v 267.1 (42.4) µmol HClO/ml) remained unchanged. Conclusion: For three hours after PRC transfusion, plasma NTBI is significantly increased in preterm infants, but this is not associated with significant changes in oxidative stress.